(untitled) (Research, Society and Development, 2021)
This study aimed to investigate the problem: do teachers who teach science today know how the brain works and how is learning consolidated? As well, what are the pedagogical activities that make the student be motivated to learn? To answer the question, it was investigated how neuroscience and its concepts emerged, covering types of memory and the importance of attention in learning and, afterwards, neuroscience and Science Teaching covering how neuroscience emerged in Education, its applications in the classroom, what the National Common Curricular Base portrays and what reveals the latest studies in the area in relation to neuroscience and learning. Therefore, this study is qualitative and exploratory, which seeks to answer a problem. It is concluded by the findings, that the teacher does not know the functioning of the brain and how the learning is consolidated, as well as what leads the student to be motivated. Regarding pedagogical actions, which activate the brain to learn, several authors state that playful activities, the use of videos, images, sounds, body movements, challenges, and other types of actions, promote neurocognitive stimuli.